TRPV4 modulates inflammatory responses and apoptosis in enteric glial cells triggered by Clostridioides difficile toxins A and B - Dvison de Melo Pacífico; Deiziane Viana da Silva Costa; Maria Lucianny Lima Barbosa; Conceição Silva Martins Rebouças; Simone de Goes Simonato; Cirle Alcantara Warren; Maria Luana Gaudencio dos Santos Morais; Renata Ferreira de Carvalho Leitao; Gerly Anne de Castro Brito (Journal of Inflammation)
Abstract Clostridioides difficile, a spore-forming anaerobic bacterium, is the primary cause of hospital antibiotic-associated diarrhea. Key virulence factors, toxins A (TcdA) and B (TcdB), significantly contribute to C. difficile infection (CDI). Yet, the specific impact of these toxins, particularly on enteric glial cells (EGCs), still needs to be fully understood. This study examines the role of the transient receptor potential vanilloid 4 (TRPV4), a calcium-permeable channel, in the inflammatory response and apoptosis of EGCs induced by TcdA and TcdB and evaluates TRPV4 expression in the cecum and colon of infected mice. EGCs were treated with TcdA (50ng/mL) or TcdB (1ng/mL) for 18 h, with or without the TRPV4 antagonist RN-1734 (100 µM), to assess TRPV4 gene and protein levels, inflammatory markers, and cell death. C. difficile infected mice were euthanized on day 3 post-infection for TRPV4 expression in the cecum and colon. Findings reveal that EGCs naturally express TRPV4, increasing its expression by TcdA and TcdB exposure. CDI significantly upregulates TRPV4 in the cecum and colon’s submucosal and myenteric plexus regions. TRPV4 mediates TNF-α release in EGCs and is partially involved in the increase in IL-6 gene expression triggered by these toxins. Our results highlight TRPV4’s role in triggering EGC apoptosis via caspase 3 activation and inhibiting the reduction of Bcl-2, an anti-apoptotic protein in EGCs caused by C. difficile toxins. These results highlight TRPV4’s significant role in CDI pathogenesis and its potential as a therapeutic target to counteract the detrimental effects of C. difficile toxins on enteric glia.